2022
DOI: 10.3390/pathogens11070723
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of Salmonella enterica Serovar Choleraesuis in Free Ranging European Wild Boar in Sweden

Abstract: Following the first detection of Salmonella enterica subsp. enterica, serovar Choleraesuis (S. Choleraesuis) in a Swedish pig herd for more than 40 years and subsequent detection of the same serotype in an enclosure with kept wild boar, a national surveillance for S. Choleraesuis in free living wild boar was launched. A total of 633 wild boar sampled within the active and the enhanced passive surveillance were examined for Salmonella enterica serovars by culture. Of these, 80 animals were culture positive for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In Sweden, it was reported that, out of a total of 633 wild boars sampled within surveillance programs, 80 animals tested positive for S. Choleraesuis var. Kunzendorf, and all sequenced isolates clustered with those isolated from domestic pig farms in the same region [44]. This highlights the importance of implementing strict biosecurity measures to prevent and hinder the possibility of transmission events from the wild boar population to domestic pigs [50].…”
Section: Overviewmentioning
confidence: 73%
See 2 more Smart Citations
“…In Sweden, it was reported that, out of a total of 633 wild boars sampled within surveillance programs, 80 animals tested positive for S. Choleraesuis var. Kunzendorf, and all sequenced isolates clustered with those isolated from domestic pig farms in the same region [44]. This highlights the importance of implementing strict biosecurity measures to prevent and hinder the possibility of transmission events from the wild boar population to domestic pigs [50].…”
Section: Overviewmentioning
confidence: 73%
“…Kunzendorf was detected for the first time in swine herds in Denmark between 2012 and 2013, with reported outbreaks characterized by high mortality rates (20-30%) [39]. Moreover, after 40 years of absence, S. Choleraesuis was reported in 5 pig herds in Sweden in 2022 [44].…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Choleraesuis variant Kunzendorf is highly prevalent in North America and Asia but is relatively rare in the EU and Australia. However, multiple outbreaks in wild boars and pig herds have been recently reported in Europe including Serbia, 2 Denmark, 3 Sweden, 4 Italy 5 and Spain. 6 Wild boars were hypothesized to play a prominent role in the interplay between Salmonella, livestock and the human population.…”
Section: Introductionmentioning
confidence: 99%
“…S. Choleraesuis is a widely disseminated serotype ( Chiu et al, 2004 ) and is the most common cause of nontyphoid Salmonella infection in Thailand ( Luk-In et al, 2018 ). In Europe, the growing number of S. Choleraesuis infections among wild boars has attracted research attention ( Longo et al, 2019 ; Papic et al, 2021 ; Ernholm et al, 2022 ). In humans, this pathogen has higher invasiveness and is thus a greater health threat than other serotypes ( Cohen et al, 1987 ).…”
Section: Introductionmentioning
confidence: 99%